2017
DOI: 10.18203/2394-6040.ijcmph20173333
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anaemia and its epidemiological correlates among women of reproductive age group in an urban slum of Mumbai

Abstract: Background: Anaemia is a major public health problem affecting children, adolescent, women of reproductive age groups and lactating mothers worldwide. As per NFHS-IV data, prevalence of anaemia in India is 53%. This study was done to assess the prevalence of anaemia and its epidemiological correlates among women in reproductive age groups in an urban slum of Mumbai. Methods: This community based cross-sectional study was carried out in an urban slum in Mumbai. Total 315 women in the reproductive age groups (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
3
10
0
Order By: Relevance
“…Menstruation is among the factors that could be associated with anemia due to periodic blood loss [12], which explains the rationale of the classification of age groups in this study, provided that the average year of menopause among Malaysian women is 50 years old [12]. On the other hand, a study in India reported that women from the age group below 25 years old tended to be more affected by anemia [16]. A possible explanation for the variation might be the common occurrence of teenage pregnancy in India considering that half of them usually fall pregnant with a maternal age below 20 years old, while more than one fourth fall pregnant before 18 years old [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menstruation is among the factors that could be associated with anemia due to periodic blood loss [12], which explains the rationale of the classification of age groups in this study, provided that the average year of menopause among Malaysian women is 50 years old [12]. On the other hand, a study in India reported that women from the age group below 25 years old tended to be more affected by anemia [16]. A possible explanation for the variation might be the common occurrence of teenage pregnancy in India considering that half of them usually fall pregnant with a maternal age below 20 years old, while more than one fourth fall pregnant before 18 years old [35].…”
Section: Discussionmentioning
confidence: 99%
“…Existing research recognizes a high prevalence of anemia among the vegetarian population. For example, a cross-sectional study was conducted among women aged 15 to 49 years in an urban slum from Mumbai, India who had been taking a mixed diet (47.4%), and the results showed that they were less anemic than those who were vegetarians (64.4%) [16]. Another cross-sectional study in Rajasthan, India showed that all of the female vegetarians were anemic [17].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the EDHS report of 2016 (23%) [ 11 ], a study conducted in Sidama zone of Southern Ethiopia (21.3%) [ 25 ]. On the other hand, it is lower than other studies conducted in Coimbatore district, India (64.4%) [ 26 ], in urban slums of Lucknow city, India (69%) [ 27 ], in Bursa, Turkey (32.8%) [ 28 ], Tanzania (39.6%) [ 29 ], Bangladesh (41.3%) [ 30 ], in urban slum of Mumbai, India (49.5%) [ 31 ], and Nepal city (37.6%) [ 18 ]. Moreover, the prevalence of anemia in this study was higher than those of the studies conducted in Jimma, Ethiopia (16%) [ 32 ], 2011's WHO report for Ethiopia (19%) [ 12 ], in rural Tabas, Iran 13.8% [ 33 ], and Vietnam 19.7% [ 34 ].…”
Section: Discussionmentioning
confidence: 78%
“…This undernutrition, in turn, leads to the development of anemia. However, other studies in Jimma, Ethiopia, and in an urban slum of Mumbai, India, showed that age category between 25 and 35 had a greater risk of developing anemia than other age groups [ 31 , 32 ]. Age category also significantly associated with anemia in a study conducted in Nepal city, but they found that being in the young age category was a risk factor for anemia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation